FlowerMate: Multidimensional reciprocity and inaccuracy indices for style‐polymorphic plant populations - Violeta Simón‐Porcar; A. Jesús Muñoz‐Pajares; Juan Arroyo; Steven D. Johnson (Applications in Plant Sciences)
Abstract Premise Heterostyly in plants promotes pollen transfer between floral morphs, because female and male sex organs are located at roughly reciprocal heights within the flowers of each morph. Reciprocity indices, which assess the one‐dimensional variation in the height of sex organs, are used to define the phenotypic structure of heterostyly in plant populations and to make inferences about selection. Other reciprocal stylar polymorphisms (e.g., enantiostyly) may function in a similar manner to heterostyly. In‐depth assessment of their potential fit with pollinators requires accounting for the multidimensional variation in the location of sex organs. Methods and Results We have adapted the existing reciprocity indices used for heterostylous plant populations to incorporate multidimensional data. We illustrate the computation of the adapted and original indices in the freely available R package FlowerMate. Conclusions FlowerMate provides fast computation of reliable indices to facilitate understanding of the evolution and function of the full diversity of reciprocal polymorphisms.